2020
DOI: 10.2139/ssrn.3757905
|View full text |Cite
|
Sign up to set email alerts
|

Cryogel-Integrated Biochip for Liver Tissue Engineering

Abstract: Microfluidic systems and polymer hydrogels have been widely developed for tissue engineering. Yet only a few tools combining both approaches, especially for in vitro liver models, are being explored. In this study, an alginate-based cryogel-integrated biochip was engineered for dynamic hepatoma cell line culture in three dimensions (3D). The alginate cryogel was covalently cross-linked in the biochip at subzero temperatures (T < 0 °C) to create a scaffold with high mechanical stability and an interconnected ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This microsystem was utilized for short-and long-term cultures of cell lines but also primary (rat and human hepatocytes) and stem cells (Essaouiba et al, 2022;Prot et al, 2011aProt et al, , 2011bLegendre et al, 2013;Jellali et al, 2016;Danoy et al, 2021;Etxeberria et al, 2022). It has already been used successfully for many toxicity and metabolic studies Jellali et al, 2018Jellali et al, , 2021Prot et al, 2011b), and numerous coculture models (Bricks et al, 2015;Danoy et al, 2021;Essaouiba et al, 2020;Prot et al, 2014;Zeller et al, 2017). Recently, hydrogel and hydroscaffolds were integrated in the biochip to promote liver cell organization in 3D spheroids/organoids (Boulais et al, 2020;Messelmani et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This microsystem was utilized for short-and long-term cultures of cell lines but also primary (rat and human hepatocytes) and stem cells (Essaouiba et al, 2022;Prot et al, 2011aProt et al, , 2011bLegendre et al, 2013;Jellali et al, 2016;Danoy et al, 2021;Etxeberria et al, 2022). It has already been used successfully for many toxicity and metabolic studies Jellali et al, 2018Jellali et al, , 2021Prot et al, 2011b), and numerous coculture models (Bricks et al, 2015;Danoy et al, 2021;Essaouiba et al, 2020;Prot et al, 2014;Zeller et al, 2017). Recently, hydrogel and hydroscaffolds were integrated in the biochip to promote liver cell organization in 3D spheroids/organoids (Boulais et al, 2020;Messelmani et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical properties of alginate gels obtained by ionic cross-linking with Ca 2+ are difficult to control. To overcome this, Boulais et al performed a covalent cross-linking with chemical agents, the adipic acid dihydrazide (AAD), a symmetrical molecule with primary amines at each end, and EDC to obtain alginate cryogels [74]. The carboxylic group of alginate monomers was first activated by EDC, followed by reaction with AAD.…”
Section: Alginatesmentioning
confidence: 99%
“…It was found that the optimal parameters for the preparation of the cryogel are a concentration of alginate of 1% and 2% (w/v), and mole ratios AAD:EDC of 1:1 and 1:2, respectively. These cryogels have a macroporous structure, and their mechanical properties correspond to those of a healthy liver [74].…”
Section: Alginatesmentioning
confidence: 99%